Occupational Therapy for Upper Limb Post-Stroke Sensory Impairments: A Survey. (October 2013) - Doyle, Susan; Bennett, Sally; Gustafsson, Louise
Purpose: Upper limb post-stroke sensory impairments have an impact on a significant number of stroke survivors. There is limited research in this area and it is unclear how occupational therapists are addressing sensory impairments in clinical practice. This study aimed to investigate the clinical practice patterns of occupational therapists, perceived barriers to providing interventions and information sources used when addressing upper limb post-stroke sensory impairments. Methods: A survey was sent to 500 randomly selected occupational therapists in the United States. Findings: The majority of the 145 respondents reported frequently assessing sensation, and half reported providing interventions for sensory impairments. Interventions primarily focused on providing passive sensory stimulation followed by compensatory strategies. Most therapists provided patient/caregiver education about safety. Therapists cited lack of knowledge and skills, patients' short length of stay and lack of time as barriers to utilizing interventions. Most therapists reported not being up to date with current research and requested continuing education to support practice. Conclusion: This survey established a profile of American occupational therapists' practice with people with upper limb post-stroke sensory impairments. Therapists have a need for information and training in all aspects of the management of upper limb post-stroke sensory impairment. Further research, evaluating the effectiveness of interventions and exploring therapists' clinical decision making when choosing interventions, is also needed.